Circulating FGF21 Levels in Human Health and Metabolic Disease - Keuper, Michaela; Häring, Hans-Ulrich; Staiger, Harald (Experimental and Clinical Endocrinology & Diabetes, 2019)
Human fibroblast growth factor 21 (FGF21) is primarily produced and secreted by the liver as a hepatokine. This hormone circulates to its target tissues (e. g., brain, adipose tissue), which requires two components, one of the preferred FGF receptor isoforms (FGFR1c and FGFR3c) and the co-factor beta-Klotho (KLB) to trigger downstream signaling pathways. Although targeting FGF21 signaling in humans by analogues and receptor agonists results in beneficial effects, e. g., improvements in plasma lipids and decreased body weight, it failed to recapitulate the improvements in glucose handling shown for many mouse models. FGF21’s role and metabolic effects in mice and its therapeutic potential have extensively been reviewed elsewhere. In this review we focus on circulating FGF21 levels in humans and their associations with disease and clinical parameters, focusing primarily on obesity and obesity-associated diseases such as type-2 diabetes. We provide a comprehensive overview on human circulating FGF21 levels under normal physiology and metabolic disease. We discuss the emerging field of inactivating FGF21 in human blood by fibroblast activation protein (FAP) and its potential clinical implications.
Keywords: hepatokine; metabolic disease; obesity; diabetes